Pesan Moral dalam Sinetron Dunia Terbalik RCTI Episode 1-5 Melalui Semiotika Roland Barthes - I'anatul Millah; Ramdani; Nurma Fitriani; Nur Asia (Pusat Studi Gender dan Anak (PSGA) Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Sultan Maulana Hasanuddin Banten, 2023)
In the midst of technological developments and diverse entertainment choices, television remains one of the media that people often use. Television is still popular because it is easy to access and free. One program that people like is soap operas. Soap operas are a means of entertainment in audiovisual form which tend to be broadcast in several episodes. One of the soap operas that has lasted quite a long time is Dunia Terbalik. As of November 2023, the soap opera Dunia Terbalik has reached 2900 episodes. This soap opera is the opposite of the reality of the role between wife and husband in the cultural formation of Indonesian society. This research uses a qualitative descriptive approach using Roland Barthes' semiotic analysis. The results of this research show that the meaning of gender exchange is more dominant in several parts of the scenes in the soap opera Dunia Terbalik. Apart from that, morals and justifications for the conditions of reality are formed very ideally so that they reflect the expectations of the existence of the existing culture. The roles played as husband and wife are exchanged in an ideal construction as part of a new reality conveyed through scenes within existing scenes.